Pelatihan Guide bagi Borneo Historical Community (BHC) dalam Memperkenalkan Situs Bersejarah di Kota Banjarmasin - Sriwati Sriwati; Rochgiyanti Rochgiyanti; Helmi Akmal; Zainal Abidin; Fathurrahman Fathurrahman; Jamaludin Jamaludin (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the knowledge, experience, and skills of BHC members as the guide in introducing historical sites in the city of Banjarmasin. The service activity method used is training, discussion, and practice. Training and discussion are carried out to consolidate material on guiding technique, while the practice is carried out to provide experience and skills as the guide for trainees. The participants who took part in this training were administrators and members of the BHC as many as 25 people. The evaluation instrument for this activity uses pre-test and post-test which are analyzed descriptively. The results of this community service activity show that from the cognitive aspect the participants already have very good knowledge because there has been a significant increase in the score of pre-test and post-test. Based on the results of observing the affective aspect of the participants, it can be said that they were good during the training activities. Likewise, the psychomotor aspect can be said to be good based on the results of observations when participants practice being guides. In conclusion, the training participants experience a significant increase both cognitively, affectively, and in the psychomotor aspect in mastering the material to become a guide for introducing the historical sites of the city of Banjarmasin.